2016
DOI: 10.1042/cs20160062
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in DOCA-salt-hypertensive mice: role of neuronal nitric oxide synthase-derived hydrogen peroxide

Abstract: Endothelial dysfunction is a common problem associated with hypertension and is considered a precursor to the development of micro- and macro-vascular complications. The present study investigated the involvement of nNOS (neuronal nitric oxide synthase) and H2O2 (hydrogen peroxide) in the impaired endothelium-dependent vasodilation of the mesenteric arteries of DOCA (deoxycorticosterone acetate)-salt-hypertensive mice. Myograph studies were used to investigate the endothelium-dependent vasodilator effect of AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 50 publications
1
22
1
1
Order By: Relevance
“…nNOS expression and activity have previously been demonstrated in the vasculature including in mesenteric arteries . Previous studies have demonstrated the importance of nNOS on arterial tone, with changes in/ablation of nNOS expression , or with overexpression of PMCA4 as a regulator of nNOS activity or in disease states such as hypertension . In contrast, we found no significant effect of inhibition of nNOS with VLN or NOS with LNNA alone on BP or on arterial contractility, respectively.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…nNOS expression and activity have previously been demonstrated in the vasculature including in mesenteric arteries . Previous studies have demonstrated the importance of nNOS on arterial tone, with changes in/ablation of nNOS expression , or with overexpression of PMCA4 as a regulator of nNOS activity or in disease states such as hypertension . In contrast, we found no significant effect of inhibition of nNOS with VLN or NOS with LNNA alone on BP or on arterial contractility, respectively.…”
Section: Discussioncontrasting
confidence: 76%
“…In WT mice, we showed that the effects of acute PMCA4 inhibition with ATA on BP and isolated arterial contractility were not observed in the presence of inhibitors of nNOS, suggesting these effects of ATA are also via a nNOS-dependent mechanism(s). nNOS expression and activity have previously been demonstrated in the vasculature including in mesenteric arteries [17,[42][43][44][45]. Previous studies have demonstrated the importance of nNOS on arterial tone, with changes in/ablation of nNOS expression [14], or with overexpression of PMCA4 as a regulator of nNOS activity [17] or in disease states such as hypertension [42,45].…”
Section: Discussionmentioning
confidence: 98%
“…; Silva et al. ), and iNOS can be induced in endothelium with knock‐out of the other NOS isoforms (Takaki et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the oxidative stress is the major cause of endothelial dysfunction in several forms of vascular diseases, mainly via disruption of NO· signaling pathway (Drummond et al, 2011; Silva et al, 2016). Therefore, enhanced superoxide anion dismutation through the SOD mimetic can prevents the inactivation of NO· and formation of the highly reactive intermediate peroxynitrite (Weaver et al, 2005), and thus yielding augmented H 2 O 2 concentration, an endothelium-dependent relaxing factor in aorta (Capettini et al, 2008, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…nNOS uncoupling has been implicated in several endothelium-dependent vascular disorders such as, in mesenteric artery of DOCA-salt hypertensive mice (Silva et al, 2016), thoracic aorta subjected to experimental atherosclerosis model (Capettini et al, 2011) and penile arteries of obese Zucker rat (Sánchez et al, 2012). Accordingly, deficient mice of B 1 -kinin receptor has been described to aggravate atherosclerosis and the development of abdominal aorta aneurysms in ApoE −/− mice under cholesterol rich-diet (Merino et al, 2009).…”
Section: Discussionmentioning
confidence: 99%